Understanding Labor Market Discrimination Against Transgender People: Evidence from a Double List Experiment and a Survey - Aksoy, Billur; Carpenter, Christopher S.; Sansone, Dario (Management Science, 2024)
Using a double list experiment designed to elicit views free from social desirability bias, we find that support in the United States for transgender people in the labor market is significantly overreported by 8%–10%. After correcting for this overreporting, we still find that over two-thirds of respondents would be comfortable with a transgender manager and support employment nondiscrimination protection for transgender people. However, respondents severely underestimate this level of support. We also show that stated labor market support for transgender people is lower than support for gay, lesbian, and bisexual people. Our results advance our understanding of employment discrimination against transgender people. This paper was accepted by Marie Claire Villeval, behavioral economics and decision analysis. Funding: Financial support from The Vanderbilt LGBTQ+ Policy Lab. is gratefully acknowledged. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.02567 .